2005
DOI: 10.1002/eat.20091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traumatic experiences and violent acts upon response to treatment of a sample of Colombian women with eating disorders

Abstract: Violent social conditions should be noted as another form of trauma with potential impact on outcome in Colombian women with eating disorders. (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 16 publications
(12 reference statements)
2
59
0
6
Order By: Relevance
“…We found this to be of relevance because ED patients, who have experienced traumatic events, more often drop out from treatment, demonstrate poorer outcomes and higher relapse rates than non-traumatized patients as studies by Rodríguez, Pérez, and García (2005) and Mahon et al (2001) have demonstrated. Because PTSD is quite often not diagnosed in routine clinical practice, a second goal of our study was to compare the rates of PTSD diagnosis in clinical practice and psychometric testing in ED patients.…”
Section: Introductionmentioning
confidence: 75%
“…We found this to be of relevance because ED patients, who have experienced traumatic events, more often drop out from treatment, demonstrate poorer outcomes and higher relapse rates than non-traumatized patients as studies by Rodríguez, Pérez, and García (2005) and Mahon et al (2001) have demonstrated. Because PTSD is quite often not diagnosed in routine clinical practice, a second goal of our study was to compare the rates of PTSD diagnosis in clinical practice and psychometric testing in ED patients.…”
Section: Introductionmentioning
confidence: 75%
“…Another form of physical selfpunishment following trauma may be the experience of an eating disorder. History of trauma has been linked with eating disorders in general (Rodriguez, Perez, & Garcia, 2005) as well as with binge eating (van Gerko, Hughes, Hamill, & Waller, 2005;Wheeler, Greiner, & Boulton, 2005) and anorexia nervosa (Schmidt, Tiller, Blanchard, Andrews, & Treasure, 1997).…”
Section: Evidence Supporting Topa Model Elementsmentioning
confidence: 99%
“…89 Such emotional distress often includes symptoms of depression 90,91 and anxiety, 92 but may also include binge eating, 93,94 anorexia nervosa, 95 or other eating disorders. 96 Such posttraumatic symptoms commonly appears acutely in the immediate aftermath of trauma but often fades with time. 45,97 Unfortunately, it can last for months or even years to come.…”
Section: Internalizing Distressmentioning
confidence: 99%